Investigation of the value of hematological biomarkers in the clinical differential diagnosis of IgG4-RD - KARADENİZ, HAZAN; GÜLER, ASLIHAN AVANOĞLU; KARDAŞ, RIZA CAN; KARADENİZ, MUZAFFER; PAŞAOĞLU, HATİCE; KÜÇÜK, HAMİT; GÖKER, BERNA; TUFAN, ABDURRAHMAN; ÖZTÜRK, MEHMET AKİF (Turkish journal of medical sciences, 2023)
IgG4- related disease (IgG4- RD) is a systemic fibroinflammatory disease whose pathogenesis has not been completely elucidated. Due to the novelty and complexity of the diagnostic criteria, it is difficult to distinguish from the diseases included in the differential diagnosis without tissue biopsy. This study aimed to discover new biomarkers that can help for disease diagnosis and its differential diagnosis by reviewing the relationships between neutrophil-lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and systemic inflammation response index (SIRI). Thirty IgG4- RD, 38 granulomatous polyangiitis (GPA), and 46 sarcoidosis patients presenting to the Rheumatology Clinic meeting the criteria of 2019 American College of Rheumatology, 2012 International Chapel Hill and 1999 American Thoracic Society meeting, respectively, and 27 healthy control subjects were included. We collected data on complete blood count with automated differential values including NLR, PLR, SII, and SIRI. The SII and PLR values were significantly higher in patients with IgG4-RD compared to healthy controls, (SII median (minmax) 572 (102-5583) vs. 434 (172-897), PLR median (min-max) 130 (56.8-546) vs. 104 (57.5- 253) p < 0.001). SII value was found to have a significant positive correlation with CRP in IgG4-RD disease (r = 0.371; p = 0.043). While SII, SIRI, NLR, PLR parameters were not significant between the IgG4-RD and sarcoidosis groups, SII, SIRI, NLR, PLR were significantly higher in patients with GPA than in IgG4-RD patients (p < 0.001). This is the first study to review the SII, SIRI, NLR, and PLR in IgG4-RD. The obtained results suggest that the SII could beused as a new tool, for differential diagnosis and activity of the IgG4-RD.